Analisis Kriminologis Terhadap Kasus Pengeroyokan Juru Parkir oleh Geng Motor “Brigez” di Cimaung, Bandung - Defianti, Fifi; Yusuf, Hudi (Media Hukum Indonesia (MHI), 2025)
The case of a motorcycle gang assault that occurred in Cimaung, Bandung Regency, on March 16, 2025, has become a public spotlight because it caused the death of a parking attendant. This study aims to analyze the criminological crime against the perpetrators of the assault that caused death, as well as to identify the legal basis used in the law enforcement process. This study uses a normative legal method with a statutory approach and a case approach. The results of the study indicate that the actions of the perpetrators have fulfilled the elements of a criminal act as regulated in Article 170 paragraph (2) 3 of the Criminal Code, and can be expanded using Articles 55 and 56 of the Criminal Code regarding involvement. If there is evidence of intent or a plan to murder, then Article 338 or 340 of the Criminal Code can be applied. Strict law enforcement against the perpetrators is expected to provide a deterrent effect and increase the public's sense of security.